2015
DOI: 10.1016/j.physletb.2015.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Ginzburg–Landau approach to inhomogeneous phases in nonlocal chiral quark models

Abstract: We analyze the presence of inhomogeneous phases in the QCD phase diagram within the framework of nonlocal chiral quark models. We concentrate in particular in the positions of the tricritical (TCP) and Lifshitz (LP) points, which are studied in a general context using a generalized Ginzburg-Landau approach. We find that for all the phenomenologically acceptable model parametrizations considered the TCP is located at a higher temperature and a lower chemical potential in comparison with the LP. Consequently, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…[46] for a review on the subject). In previous works [47,48], we have analyzed the existence of inhomogeneous condensates in the context of nonlocal models by explicitly constructing the associated phase diagrams in the mean-field approximation for a dual chiral density wave [49]. In principle, a full analysis would require to consider general spatial dependent condensates, which turns out to be a very difficult task for an arbitrary three-dimensional configuration.…”
Section: T − μ Phase Diagrammentioning
confidence: 99%
“…[46] for a review on the subject). In previous works [47,48], we have analyzed the existence of inhomogeneous condensates in the context of nonlocal models by explicitly constructing the associated phase diagrams in the mean-field approximation for a dual chiral density wave [49]. In principle, a full analysis would require to consider general spatial dependent condensates, which turns out to be a very difficult task for an arbitrary three-dimensional configuration.…”
Section: T − μ Phase Diagrammentioning
confidence: 99%
“…The Ginzburg-Landau dynamics depends on two fundamental quantities: the energy functional that gives the equilibrium phase diagram and the Onsager coefficient Γ, a time scale related to fluctuation and dissipation processes. We employed NJL-type models to obtain the energy functional; we considered a local NJL model with point-like interactions [4] and a nonlocal NJL model with finite-range interactions [30]. The results are qualitatively similar for both models, but there are interesting differences.…”
Section: Discussionmentioning
confidence: 99%
“…For the local NJL model, one has [30] α 4b = α 4 , and α 6b /5 = α 6c /3 = 2α 6d ≡ α 6 , which is the case investigated in Ref. [4].…”
Section: Chiral Order Parameters -Staticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only at the end of the 90's the possibility of new intermediate phases in the QCD phase diagram, like color superconductivity in which quark Cooper pairs are formed, began to be accepted [31] and later studied in detail in compact stars environments [32]. It has also been suggested that there may be non-homogeneous phases [33][34][35][36], and that there may be a phase of confined quarks with restored chiral symmetry (quarkyonic phase) [37][38][39]. A schematic version of the conjectured phase diagram of QCD is presented in figure 1.…”
Section: Probing Dense Matter Beyond Nucleimentioning
confidence: 99%